Wind-Induced Response of Inclined and Yawed Ice-Accreted Stay Cable Models - Songyu Cao; Himan Hojat Jalali; Elena Dragomirescu (Shock and Vibration)
During the past decades, wind-induced vibrations of bridge stay cables were reported to occur under various incipient conditions. The ice formation on stay cables is one of these conditions, which causes the ice-accreted stay cables to alter their cross section geometry, thus modifying their aerodynamic characteristics. Wind tunnel tests and several CFD simulations were performed for ice-accreted inclined bridge stay cables with two ice-accretion profiles dimensions, 0.5D and 1D, where D is the diameter of the cable. Wind-induced vibrations were analyzed experimentally for cable models with yaw inclination angles of 0°, 30°, and 60° and vertical inclination angles of 0° and 15°, for Reynolds numbers of up to 4 × 105. The aerodynamic drag and lift coefficients of the cable models and the pressure coefficients were determined from the CFD-LES simulations. The experimental results indicated that the vertical and torsional vibrations of the ice-accreted stay cables increased with the increase of the vertical and yaw angles. Also, higher vertical and torsional vibration amplitudes were measured for the case with larger ice thickness, indicating the effect of the ice accretion profile on the cable wind-induced response.